Holistic face perception in young and older adults: effects of feedback and attentional demand - Meinhardt-Injac, Bozana; Persike, Malte; Meinhardt, Günter (Frontiers in Aging Neuroscience, 2014)
Evidence exists for age-related decline in face cognition ability. However, the extents to which attentional demand and flexibility to adapt viewing strategies contribute to age-related decline in face cognition tests is poorly understood. Here, we studied holistic face perception in older (age range 65-78 years, mean age 69.9) and young adults (age range 20-32 years, mean age 23.1) using the complete design for a sequential study-test composite face task (Richler et al., 2008). Attentional demand was varied using trials that required participants to attend to both face halves and to redirect attention to one face half during the test (high attentional demand), and trials that allowed participants to keep a pre-adjusted focus (low attentional demand). We also varied viewing time and provided trial-by-trial feedback or no feedback. We observed strong composite effects, which were larger for the elderly in all conditions, independent of viewing time. Composite effects were smaller for low attentional demand, and larger for high attentional demand. No age-related differences were found in this respect. Feedback also reduced the composite effects in both age groups. Young adults could benefit from feedback in conditions with low and high attentional demands. Older adults performed better with feedback only in trials with low attentional demand. When attentional demand was high, older adults could no longer use the feedback signal, and performed worse with feedback than without. These findings suggest that older adults tend to use a global focus for faces, albeit piecemeal analysis is required for the task, and have difficulties adapting their viewing strategies when task demands are high.These results are consistent with the idea that elderly rely more on holistic strategies as a means to reduce perceptual and cognitive load when processing resources are limited (Konar et al., 2013).